A comprehensive review on pathogenesis, associations, clinical findings, and treatment of livedoid vasculopathy - Seguí, Mireia; Llamas-Velasco, Mar (Frontiers in Medicine, 2022)
Livedoid vasculopathy (LV) is a thrombo-occlusive vasculopathy that involves the dermal vessels. Clinically, it is characterized by the presence of painful purpuric ulcers on the lower extremities. Histopathologically, it shows intraluminal fibrin deposition and thrombosis, segmental hyalinization, and endothelial proliferation. It is important to notice that the term “atrophie blanche” is descriptive and it includes not only patients with LV but also patients with a combination of vasculitis and vasculopathy, that is, LV and medium-sized vasculitis such as cutaneous polyarteritis nodosa (PANc). Diagnosis is based on a proper clinicopathological correlation, excluding the main differential diagnosis and considering vasculitis as a mimicker or concomitant diagnosis. Coagulation disorders must also be studied although they are not found in all LV. Its frequency is reviewed as well. Treatment of LV is challenging, and different therapies have been attempted. Among them, pain management, wound care, control of cardiovascular risk factors, and both antiplatelets and anticoagulants, mostly rivaroxaban, are the main therapies used. These different therapies as well as their degree of evidence are reviewed.